2018
DOI: 10.1590/s0100-83582018360100037
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Role of Row Spacing and Adjuvant to Reduce Herbicide Dose in Maize Under Semi-Arid Conditions

Abstract: as an adjuvant along with weedy check in maize sown at 60 and 75 cm row spacing. Alkyl ether sulphate increased weed control efficacy (13-35%) of the pre-mixed herbicide. Herbicide along with adjuvant provided effective weed control at 60 cm as compared to 75 cm apart sown maize. The most effective control of weeds, and increase in maize grain yield (33-45% as compared to non-treated control) and net income were obtained by the pre-mixed herbicide at 539.4 g a.i. ha -1 (75% of recommended rate) with adjuvant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A study by Khaffagy et al [2020], in turn, reveals that the use of a dose of nicosulfuron reduced by 50% together with adjuvant did not give satisfactory results, but the application of this herbicide at a dose reduced by 25% in combination with adjuvant caused a significant reduction in weed biomass in comparison with the dose of the herbicide applied alone. Nadeem et al [2018] also demonstrated the rationale for reducing the dose of herbicide (atrazine + mesotrione + halosulfuron-methyl) by 25% applied in combination with an adjuvant. In this research, the doses of nicosulfuron reduced by 20% and 40% and applied with the adjuvants showed weed control effectiveness similar to that produced by the full dose of the herbicide in all years of the study.…”
Section: Discussionmentioning
confidence: 93%
“…A study by Khaffagy et al [2020], in turn, reveals that the use of a dose of nicosulfuron reduced by 50% together with adjuvant did not give satisfactory results, but the application of this herbicide at a dose reduced by 25% in combination with adjuvant caused a significant reduction in weed biomass in comparison with the dose of the herbicide applied alone. Nadeem et al [2018] also demonstrated the rationale for reducing the dose of herbicide (atrazine + mesotrione + halosulfuron-methyl) by 25% applied in combination with an adjuvant. In this research, the doses of nicosulfuron reduced by 20% and 40% and applied with the adjuvants showed weed control effectiveness similar to that produced by the full dose of the herbicide in all years of the study.…”
Section: Discussionmentioning
confidence: 93%
“…Most of this research was conducted with agronomic crops within an IWM system where practices that increase crop competitiveness are incorporated. For example, Nadeem et al (2018) showed that by reducing corn row space and proper adjuvant selection, one could decrease herbicide cost and environmental damage by reducing the herbicide application rate. Zhang et al (2000) examined previously published research on below labeled rate herbicide applications in corn, soybean, and wheat production over large geographic and temporal scales and concluded that using herbicides at below labeled rates was more successful when weed pressure was low, when done in conjunction with interrow cultivation, and when corn was grown rather than soybean or wheat.…”
Section: Bmp 5: Optimal Herbicide Rate and Application Timingmentioning
confidence: 99%